1993
DOI: 10.2307/1941829
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Sensory and Postingestional Repellents in Starlings: Methyl Anthranilate and Sucrose

Abstract: Ingestion of concentrated sucrose solutions causes sickness in sucrase-deficient birds. As a result, some suggest that sucrose may represent an environmentally safe avian repellent. In the present experiments, we compared the repellency of sucrose to that of methyl anthranilate (MA), a known avian repellent. We also tested mixtures of sucrose and MA to investigate whether repellency could be enhanced, relative to sucrose or MA presented alone. The results showed that the MA was strongly avoided in both drinkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…2002), the role of dispersal‐phase VOCs in attracting or repelling birds is completely unexplored. We found methyl anthranilate [a bird‐ and mammal‐repellent compound (Mason, Adams & Clark 1989; Clark & Mason 1993; Nolte, Mason & Clark 1993)] in the gall figs of both F. hispida (in very high quantities) and F. exasperata but none in the seed figs of either species. Figs are thus possibly using specific compounds to repel dispersal agents from gall figs and to facilitate preferential consumption of seed figs, as earlier predicted.…”
Section: Discussionmentioning
confidence: 91%
“…2002), the role of dispersal‐phase VOCs in attracting or repelling birds is completely unexplored. We found methyl anthranilate [a bird‐ and mammal‐repellent compound (Mason, Adams & Clark 1989; Clark & Mason 1993; Nolte, Mason & Clark 1993)] in the gall figs of both F. hispida (in very high quantities) and F. exasperata but none in the seed figs of either species. Figs are thus possibly using specific compounds to repel dispersal agents from gall figs and to facilitate preferential consumption of seed figs, as earlier predicted.…”
Section: Discussionmentioning
confidence: 91%
“…Methyl anthranilate acts as a primary repellent (Rogers 1974). Primary repellents do not require learning, because they are based on congenital avoidance of irritating stimuli (Clark and Mason 1993). Successful delivery strategies target the animal's receptor fields, such as mucous membranes of the eyes, mouth and nose.…”
mentioning
confidence: 99%
“…Based on the Agricultural Research Services' National Nutrient Database for Standard Reference (release 24) blueberries contain 9.96 g of sugar per 100 g with 1% of that sugar being sucrose, whereas sweet corn contains 6.26 g sugar per 100 g with 14.2% of that sugar being sucrose. Martinez del Rio et al (1988) showed that starlings lack sucrase, the enzyme needed to hydrolyze sucrose, and Avery et al (1995) showed that starlings will respond negatively to artificial fruits having 12.8% sucrose, but starlings show no difference in consumption for solutions below 10% sucrose (Clark and Mason, 1993). We believe that the inability to digest sucrose may explain the difference in consumption of the two-test fruit diets at similar levels of repellent.…”
Section: Fruit/sucrose Matrixmentioning
confidence: 76%
“…The anthraquinone residue levels on the sweet corn in our starling experiment were lower or similar to those reported for the Carlson et al (2013) red-winged blackbird experiment however, consumption of sweet corn by starlings in our experiment decreased for both treated and untreated groups as anthraquinone concentration increased. Based on previous studies (Clark and Mason, 1993;Avery et al, 1995) it is possible that there is an interaction between the sucrose levels of the sweet corn and the anthraquinone levels that resulted in decreased consumption of both treated and untreated sweet corn. The results of our fruit experiments led us to evaluate the SucraShield product for efficacy as a chemical repellent for starlings.…”
Section: Fruit/sucrose Matrixmentioning
confidence: 99%